Exploring Collected Intelligence from Untappd to Support the Location Decision for New SMEs - Silva, Thiago H; Graeml, Alexandre R (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
Small and medium-sized enterprises (SMEs) usually have little budget for market research. That prevents them from developing sophisticated surveys or carrying out focus group sessions with current and potential customers to better understand their needs and wishes. Social media may be a rich source of information to support sound business decision making. This paper discusses the possibility of collecting data that people share in messages on social media and analyzing their content in order to build relevant knowledge for strategic business decisions, among which, location decisions. To exemplify that, we collected and analyzed messages generated by Brazilian users of Untappd, a mobile phone app for sharingbeerdrinkingexperiences. Amongotherthings,itwasvery easy to notice that users from a few cities in the country have developed a more sophisticated taste for beer and are keen to trynew types of beer and tell their friends about it. Is information like that useful for an entrepreneur who wishes to settle a new small craft beer business and needs to decide on the best place to do it? We believe so.